2019
DOI: 10.1299/jbse.18-00535
|View full text |Cite
|
Sign up to set email alerts
|

Capture event of platelets by bolus flow of red blood cells in capillaries

Abstract: Studies on platelet margination have shown that the platelets can effectively marginate at the microvessel wall in a multi-file flow of red blood cells (RBCs), whereas axially migrated RBCs push platelets toward the wall. However, it is unclear whether these results can be extended to capillaries, which potentially cause a single-file line of RBCs, or a so-called bolus flow. Our previous numerical results (Takeishi and Imai, 2017) showed that microparticles with a diameter of 1 µm (1-µm-MPs) were captured by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Experimental studies found that the degree of margination is affected by several factors such as the volume concentration of RBCs (hematocrit, Ht), channel size, flow rate, and RBC deformability [7][8][9][10][11][12]. The features of margination Micromachines 2021, 12, 1175 2 of 11 found in the experiments were well reproduced by numerical simulations, and it was elucidated that platelets in the RBC core are expelled toward the vessel wall by their random hydrodynamic interactions with surrounding RBCs under the influence of shear as well as volume exclusion, resulting in a high concentration of platelets in the CFL [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Experimental studies found that the degree of margination is affected by several factors such as the volume concentration of RBCs (hematocrit, Ht), channel size, flow rate, and RBC deformability [7][8][9][10][11][12]. The features of margination Micromachines 2021, 12, 1175 2 of 11 found in the experiments were well reproduced by numerical simulations, and it was elucidated that platelets in the RBC core are expelled toward the vessel wall by their random hydrodynamic interactions with surrounding RBCs under the influence of shear as well as volume exclusion, resulting in a high concentration of platelets in the CFL [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 80%
“…A number of numerical and model studies have been performed to elucidate the mechanism of margination of platelets in blood flow [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Crowl and Fogelson [14] conducted 2D computations to describe the development of platelet margination as a drift-diffusion process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this problem require heavy computational resources, we resort to GPU computing, using the lattice-Boltzmann method for the inner and outer fluid and the finite element method to follow the deformation of the RBC membrane. The models have been successfully applied to the analysis of hydrodynamic interactions between RBCs-leukocyte (Takeishi et al 2014),circulating tumor cell (Takeishi et al 2015) and -microparticles/platelets (Takeishi & Imai 2017;Takeishi et al 2019) in channel flows.…”
Section: Introductionmentioning
confidence: 99%
“…In our simulation, we did not consider the flow of background medium, and also neglected the presence of red cells/platelets and solvent proteins. Since there are only a few reports on the modelling of protein activation under cellular blood flow [74][75][76], it would be interesting to study how fibrous interactions affect the suspension rheology of red blood cells (RBCs) [77] or the flow behaviours of RBCs and platelets in microvessels depending on shear rates [38,78]. In summary, we proposed a minimal mesoscopic model of protofibrils based on Brownian dynamics.…”
Section: Discussionmentioning
confidence: 99%